Development and validation of bivariate UV-visible spectroscopic method for simultaneous estimation of curcumin and piperine in their combined nanoparticulate system - Srinivas Bhairy, Ashraf Shaikh, Vivek Nalawade, Rajashree Hirlekar (Journal of Applied Pharmaceutical Science, 2021)
The purpose of the research was to develop ultraviolet (UV) spectroscopic methods to simultaneously estimate curcumin (CUR) and piperine (PIP). This method involves interpreting simultaneous equations using UV visible spectrophotometer with 1 cm matched quartz cells and methanol as a solvent based on measuring absorbance at two wavelengths of 423 and 342 nm. The method developed obeyed the law of Beer–Lambert in the concentration range of 1–7 μg/ml, with the correlation coefficient for CUR and PIP at their respective maximum wavelengths being 0.9990 and 0.9988, respectively. At an iso-absorptive point, CUR and PIP in the concentration range of 1–7 μg/ml showed a correlation coefficient of 0.9995 and 0.9988, respectively. Various validation parameters, such as precision (intraday and interday studies), limit of detection, and limit of quantitation, have been tested and found to be within the limit. The results of the method have been statistically validated. For the simultaneous estimation of CUR and PIP, a novel, simple, sensitive, fast, accurate, and economical spectrophotometric method has been developed. The method can be used to estimate the amount of CUR and PIP in a nanoparticulate system containing CUR and PIP.
Keywords: Curcumin, piperine, nanoparticulate system, spectrophotometric analysis, simultaneous equation method.